Management of Lateral Wall Insufficiency - Liu, Sara W.; Lyford-Pike, Sofia (Facial Plastic Surgery, 2023)
Lateral wall insufficiency is a commonly encountered etiology of nasal obstruction, resulting from dynamic collapse at the level of the internal or external nasal valve. Various management strategies exist to strengthen the lateral wall or stent the nasal valves to relieve nasal obstruction, and range from noninvasive devices, minimally invasive implants, or surgical reconstructive techniques. Surgical options to address the nasal valves are selected based on each patient's anatomic findings, aesthetic and functional goals, and surgeon preference. This article describes the anatomy and physiology of the nasal sidewall and nasal valves and diagnosis of lateral wall insufficiency, and provides a framework for treatment options.
Keywords: rhinoplasty; nasal valve repair; lateral wall insufficiency